The Effect of Creatine on Muscle Mass Gain: A Literature Review - Drzewiecki, Artur; Drzewiecka, Antonina; Korczak, Wiktor; Madejska, Maria; Rudzka, Aleksandra; Gaszyńska , Monika; Falkowski, Wojciech; Woźniak , Weronika; Magielski, Jakub; Krysińska , Anna (Quality in Sport, 2025)
Introduction and Purpose: Creatine, a popular ergogenic aid, enhances athletic performance by influencing muscle energy reserves, protein synthesis, and growth factors. This research aims to investigate the impact of creatine on hypertrophy, comparing different types, dosages, and training methods to determine the most effective approach for promoting muscle growth. State of Knowledge: Various creatine supplementation protocols exist, including loading phases and continuous low-dose strategies, with studies showing comparable effectiveness. Research on supplementation timing (pre- vs. post-exercise) is inconclusive. While creatine enhances adaptations to resistance training (RT), its impact on muscle hypertrophy is generally small and context-dependent, with the most significant benefits observed in younger males. The benefits of creatine supplementation with RT tend to diminish in older adults and females, highlighting the importance of realistic expectations regarding its role in muscle growth. Creatine monohydrate (CM) is the most thoroughly evaluated form, known for its safety, and well documented efficacy. Conclusion: CM consistently demonstrates efficacy in enhancing RT-induced hypertrophy without demonstrating clear supplementation protocol superiority. Modest muscle and strength gains are age- and sex-dependent, being most pronounced in younger males. Although CM remains optimal, novel forms such as malate merit further investigation. These findings highlight the importance of realistic expectations regarding creatine's role in muscle growth. Future research should consider more individual factors to optimize creatine supplementation strategies.